Structural economics in China : a three-dimensional framework for balanced growth - Xiang, Junbo, 1957- (Enrich Professional Pub., 2013)
"This book explains the concept and framework of structural economics, analyzes the characteristics, degree, and reasons for structural imbalances of China's economy in such aspects as industrial and financial sectors, balance of payments, and regional economies. It concludes that the structural imbalances of China's economy have intensified in the past two decades, which has posed severe challenges to its sustainable development."--Jacket.